2015
DOI: 10.1155/2015/835613
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prenatal One-Hour Glucose Challenge Test Values and Delivery Mode in Nondiabetic, Pregnant Black Women

Abstract: Objective. We examined the association between 1-hour glucose challenge test (GCT) values and risk of caesarean section. Study Design. A prospective cohort study recruited 203 pregnant Black women to participate. At ~28 weeks of gestation, participants underwent a routine 1-hour 50 g GCT to screen for gestational diabetes mellitus. Logistic regression was used to examine the association between 1-hour GCT value and delivery mode. Results. Of the 158 participants included, 53 (33.5%) delivered via C-section; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Obesity is strongly associated with the development of a positive OGCT and GDM 15, 16. In Oman, the prevalence of obesity (BMI > 30 kg/m 2 ) among Omani women is 23.8%, and that of overweight (BMI > 25 kg/m 2 ) is 27.3%, meaning that more than 50% of Omani pregnant women have BMIs > 25 kg/m 2 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is strongly associated with the development of a positive OGCT and GDM 15, 16. In Oman, the prevalence of obesity (BMI > 30 kg/m 2 ) among Omani women is 23.8%, and that of overweight (BMI > 25 kg/m 2 ) is 27.3%, meaning that more than 50% of Omani pregnant women have BMIs > 25 kg/m 2 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Women with one abnormal value from the OGTT ("Borderline" group in our study) have been shown to have a significantly increase risk of many adverse pregnancy outcomes including fetal overgrowth, neonatal hypoglycemia, cesarean delivery, maternal hypertensive disorders, and neonatal intensive care unit admission, with rates being comparable to women who have GD. 20 Additionally, among women who receive a "false positive" result following the 50 g, nonfasting, glucose challenge test (a test used to first screen for GD risk) but are otherwise not diagnosed with GD, also experience a greater incidence of infants born large-for-gestationalage 21,22 and adverse pregnancy outcomes such as cesarean delivery, [22][23][24] shoulder dystocia, 22,24 and antenatal death. 24 Authors recommend that mothers with such borderline results would benefit from early pregnancy lifestyle interventions to reduce this risk.…”
Section: Discussionmentioning
confidence: 99%